Ethnic enclaves and immigrant earnings growth - Casey Warman (Queen's University, Department of Economics, 2006)
The impact of living in an ethnic enclave on earnings growth of immigrants in Canada is examined using the 1981-2001 Censuses. Consistent with U.S. findings, enclaves are found to have a negative impact on the earnings growth of male immigrants. A negative impact is also found for female immigrants. Living in an enclave was found to be particularly harmful for individuals immigrating as adults, especially for females, but did not affect immigrants who arrived at a young age. Enclaves had a more negative impact on high-skilled male immigrants, especially if they had received the bulk of their education outside of Canada. Enclaves also hindered language skills.
Keywords: J15; J31; 330